2018
DOI: 10.1002/stc.2197
|View full text |Cite
|
Sign up to set email alerts
|

A new device for stress monitoring of ancient masonry buildings: Pilot study and results

Abstract: Summary The need to obtain the mechanical characteristics for analysis and understanding of the mechanical behaviour of historic buildings is highlighted. Destructive tests and non‐destructive tests are widely used for this purpose; however, they only provide a value associated with a specific instant. Structural health monitoring contributes to the monitoring of specific processes before, during, or after an intervention. Nevertheless, among the available sensors, there is a lack of devices for continuous mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…As for the stress variations, it should be said that once the SFJ test was over, a slightly decreasing slope was registered, considering stabilisation from the first of September 2017. Bearing in mind this behaviour, it is important to highlight that it is necessary to overpressurise the device to compensate for the possible relaxation over time of the material of the pressure pad and/or the readjustment of the surrounding masonry structure itself . However, in this experimental campaign, it was not necessary to perform this overpressurisation, given that the stress at the end of the SFJ test was sufficiently higher than the value of the cancelling pressure to take that effect into account (Figure ).…”
Section: Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the stress variations, it should be said that once the SFJ test was over, a slightly decreasing slope was registered, considering stabilisation from the first of September 2017. Bearing in mind this behaviour, it is important to highlight that it is necessary to overpressurise the device to compensate for the possible relaxation over time of the material of the pressure pad and/or the readjustment of the surrounding masonry structure itself . However, in this experimental campaign, it was not necessary to perform this overpressurisation, given that the stress at the end of the SFJ test was sufficiently higher than the value of the cancelling pressure to take that effect into account (Figure ).…”
Section: Experimental Validationmentioning
confidence: 99%
“…Bearing in mind this behaviour, it is important to highlight that it is necessary to overpressurise the device to compensate for the possible relaxation over time of the material FIGURE 10 Evolution of the deformations undergone for each pair of monitoring points for several stress levels of the pressure pad and/or the readjustment of the surrounding masonry structure itself. 24 However, in this experimental campaign, it was not necessary to perform this overpressurisation, given that the stress at the end of the SFJ test was sufficiently higher than the value of the cancelling pressure to take that effect into account (Figure 9).…”
Section: Response Of the Device To Loading Cyclesmentioning
confidence: 99%
“…Throughout the intervention process on the building, a detailed monitoring of the most relevant elements (arches, buttresses, domes, and walls) was done through the sensors implemented in the Subsystems 2–4. However, considering the mechanical characteristics of the materials and the magnitude of the intervention processes in the building, the article highlights the monitoring of the three most significant actuations: Execution of the passive reinforcement in the load‐bearing east wall consisting of a reinforced concrete frame (Figure a), partially closing some gaps opened in an intervention previous to the monitoring period, so enabling the communication between the east cloister to the church. The equipment utilized for the monitoring of this actuation was included in Subsystem 2. Removal of the propping system from the domes after reinforcing them (Figure b).…”
Section: Application To a Historic Masonry Buildingmentioning
confidence: 99%
“…With respect to the initial behaviour of the sensors, it should be indicated that the difference between the initial stress taken as a reference during the continuous follow‐up and the service stress value determined corresponded to the tasks of over‐pressurization of the pressure pad . After this actuation, the behaviour observed in the devices in the first stages showed a slight downward slope associated with the readjustment of the system “pressure pad—masonry structure” under maintained pressure.…”
Section: Analysis Of the Data From The Integrated Systemmentioning
confidence: 99%
See 1 more Smart Citation